Using Arts-Based Research Exercises to Foster Reflexivity in Qualitative Research (LEARNing Landscapes, 2016)
Re exivity is a ubiquitous, varied, and, at times, contentious concept in qualitative inquiry that presents challenges as we strive to understand and use the concept in our work. The authors present their collaborative understanding of re exivity using their semester-long research journals, re exivity models, collaborative poetry, and collage exercises as evidence. The article details how using arts-based research exercises in the classroom can facilitate understanding and use of the concept of re exivity.
Keywords: reflexivity; qualitative; arts-based; poetry; collage